Electron‐Lattice Synergistic Coordination for Boosting the Electro‐Optic Response of the Crystal - Jinfeng Han; Yuzhou Wang; Fei Liang; Kui Wu; Dazhi Lu; Deliang Cui; Haohai Yu; Huaijin Zhang (Advanced Science)
Abstract The electro‐optic (E‐O) response is fundamental where the refractive index of materials can be modulated by the external electric field. Up to now, E‐O modulation has become a critical technology in photonics, quantum optics, modern communication, etc. However, the design of E‐O crystals with broadband availabilities and large E‐O effect is still challenging since the E‐O response is contributed by both electrons and phonons. Here, an electron‐lattice synergistic coordination strategy is proposed for boosting the E‐O response, and with the langasite as the subject, a novel crystal La3Zr0.5Ga5Si0.5O14 (LZGS) is designed. By the rational introduction of the Zr4+ ion in the octahedral site, it is found that the E‐O response can be obviously improved attributed to the active 4d orbitals of the Zr4+ ion and the optical phonons of the flexible (ZrO6) unit. This crystal also has advantages in transparency, laser damage threshold and E‐O coefficient compared with the well‐known E‐O crystals. Moreover, broadband E‐O modulation is also demonstrated in the lasers at wavelengths from 639 to 1991 nm. These findings not only demonstrate an excellent E‐O crystal for the development of modern devices in classical and quantum fields but also provide a design strategy for boosting the E‐O response.